2018
DOI: 10.3389/fneur.2018.00694
|View full text |Cite
|
Sign up to set email alerts
|

Low Diagnostic Yield of Routine Cerebrospinal Fluid Analysis in Juvenile Stroke

Abstract: Background: The diagnostic value of cerebrospinal fluid (CSF) analysis in juvenile stroke, i.e., stroke in young adult patients, is not well studied. We sought to determine the therapeutic impact of routine CSF-analysis in young adults with acute ischemic stroke or transient ischemic attack (TIA).Methods: We abstracted data from patients with acute cerebral ischemia aged 18–45 years who were consecutively admitted to our stroke center between 01/2008 and 12/2015. We routinely performed CSF-analysis in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Moreover, the CSF-analysis, in this case, presented hyperproteinorraquia and lymphocytic pleocytosis greater than expected for an ischaemic stroke. Previous studies carried out in stroke patients showed a variable range of reactive pleocytosis up to 64 Mpt/L cell and nonspecific proteins up to 1507 mg/L in CSF [7]. In cases describing higher concentrations of cells and proteins, such as our case, pathogens causing vascular damage were found.…”
supporting
confidence: 53%
“…Moreover, the CSF-analysis, in this case, presented hyperproteinorraquia and lymphocytic pleocytosis greater than expected for an ischaemic stroke. Previous studies carried out in stroke patients showed a variable range of reactive pleocytosis up to 64 Mpt/L cell and nonspecific proteins up to 1507 mg/L in CSF [7]. In cases describing higher concentrations of cells and proteins, such as our case, pathogens causing vascular damage were found.…”
supporting
confidence: 53%
“…Pleocytosis in CSF without evidence of infection or vasculitis is frequently found, in our cohort observed in 10% in younger stroke and in 9.3% in older stroke patients. CSF pleocytosis up to 18% after stroke has been reported before, ranging up to 64 cells/µL; in our cohort, one patient had a pleocytosis of 150 cells/µL most likely due to meningeal irritation by hemorrhagic transformation of the ischemic stroke areal.…”
Section: Discussionsupporting
confidence: 54%
“…In a recent study, specific CSF changes were detected in 1.5% of juvenile cerebral ischemia (ischemic strokes and transitoric ischemic attacks (TIA) . Since two out of three patients with infectious etiologies revealed features of infection‐associated vasculitis in MRI, the authors conclude that CSF analysis in juvenile stroke should not be included in routine diagnostics .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In research studies, a broader spectrum of age strata might be useful to study age-dependent differences in mechanisms of acute ischemic stroke. The knowledge deriving from this research might also help design tailored age-related strategies of diagnostic workup in young stroke patients that allow targeted assessment and avoidance of unnecessary procedures ( 48 ).…”
Section: Discussionmentioning
confidence: 99%